Factors influencing auditory verbal therapy outcome among children with cochlear implant - Nourma Wahyu Andriani; Zulfikar Naftali; Dwi Marliyawati; Pujo Widodo; Muyassaroh (Published by Universitas Gadjah Mada, 2025)
Early intervention with cochlear implants and habilitation with auditory-verbal therapy (AVT) methods can promote better development later in childhood. A previous study reported that communication methods,educational methods, duration of communication, frequency of therapy, and type of therapy influencing the effectiveness of amplification in children based on observations from parents. The AVT assessment uses severalassessments that can help determine a child’s hearing skill level, one of which is the early learning accomplishment profile (E-LAP). The study aimed to assess the factors influencing auditory–verbal therapy (AVT) outcomes among children with cochlear implants. It was an analytical observational study with a cross-sectional design in several home therapy. The assessment was using E-LAP. Chi-square test and multivariate logistic regression were used to measure the association between categorical variables. From 52 subjects, there were 32.7% who had received their cochlear implants <3 yr, 67.3% ≥3 yr, 51.9% ≥3 yr using cochlear implant, 53.8% good family participation, 51.9% had undergraduate parents, 71.2% had a profound hearing before implant, 86.5% underwent routine therapy, and 55.8% had a good outcome in AVT. This study showed age of implantation (p= 0.043), optimal family participation (p=0.006), and frequency of AVT (p= 0.002) were related to the outcomes of AVT. From multivariate logistic regression the duration of implant use was the most related (p=0.008). In conclusion, age of implantation, duration of implant use, family participation, and frequency of AVT are related to the outcomes of AVT.